Ford Madox Ford and the Misfit Moderns Edwardian Fiction and the First World War - Hawkes, R. (Palgrave Macmillan UK : Imprint: Palgrave Macmillan, 2012)
Ford Madox Ford is a major modernist writer, yet many of his works do not conform to our assumptions about modernism. Examining ways in which he, alongside other 'misfit moderns', undermines 'stabilities' we expect from novels and memoirs, this book poses questions about the nature of narrative and the distinction between modernism and modernity.